Infants' Daily Experience With Pets and Their Scanning of Animal Faces - Hurley, Karinna; Oakes, Lisa M. (Frontiers in Veterinary Science, 2018)
Very little is known about the effect of pet experience on cognitive development in infancy. In Experiment 1, we document in a large sample (N = 1270) that 63% of families with infants under 12 months have at least one household pet. The potential effect on development is significant as the first postnatal year is a critically important time for changes in the brain and cognition. Because research has revealed how experience shapes early development, it is likely that the presence of a companion dog or cat in the home influences infants’ development. In Experiment 2, we assess differences between infants who do and do not have pets (N = 171) in one aspect of cognitive development: their processing of animal faces. We examined visual exploration of images of dog, cat, monkey, and sheep faces by 4-, 6-, and 10-month-old infants. Although at the youngest ages infants with and without pets exhibited the same patterns of visual inspection of these animals faces, by 10 months infants with pets spent proportionately more time looking at the region of faces that contained the eyes than did infants without pets. Thus, exposure to pets contributes to how infants look at and learn about animal faces.